2011
DOI: 10.1007/s12541-011-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of traffic environment and cognitive workload on older drivers’ behavior in simulated driving

Abstract: As the use of in-vehicle technologies became more popular, there is concern about a concomitant increase in driver distraction arising from their use. While the introduction of voice recognition systems is intended to reduce the distraction due to manual operation of these units, a significant proportion of the distraction associated with their use may arise not from the manual manipulation but rather the cognitive consequences. It is also known that the risk of inattentive driving varies with age. In this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 19 publications
2
25
1
Order By: Relevance
“…This indicates drivers tend to take more micro-steering movements when engaged in a cognitive load task, and this type of activity increased with the level of cognitive load. This finding was also consistent with results from previous studies (Engström et al, 2005;Son et al, 2011). Gaze concentration: There was a significant main effect of task demand (F(2.23, 55.8) =8.093, p=0.001, =0.245) on gaze concentration, as shown in Fig.…”
Section: Driving Performancesupporting
confidence: 92%
See 2 more Smart Citations
“…This indicates drivers tend to take more micro-steering movements when engaged in a cognitive load task, and this type of activity increased with the level of cognitive load. This finding was also consistent with results from previous studies (Engström et al, 2005;Son et al, 2011). Gaze concentration: There was a significant main effect of task demand (F(2.23, 55.8) =8.093, p=0.001, =0.245) on gaze concentration, as shown in Fig.…”
Section: Driving Performancesupporting
confidence: 92%
“…On the other hand, many studies indicate that cognitive distraction leads to a reduction in the vehicle's standard deviation of lateral position (SDLP), but there is currently a divergence in views regarding whether such reductions should be interpreted as impaired (Mehler, Reimer, Coughlin, & Dusek, 2009;Reimer, 2009) or improved (Engström, Johansson, & Östlund, 2005;He, McCarley, & Kramer, 2014;He & McCarley, 2011;Jamson et al, 2005;Kaber, Liang, Zhang, Rogers, & Gangakhedkar, 2012;Liang et al, 2010;Son, Lee, & Kim, 2011) driving performance. In addition, studies have found this reduction in SDLP to be accompanied by a higher gaze concentration towards the road centre (Cooper, Medeiros-Ward, & Strayer, 2013;Victor, Harbluk, & Engstrom, 2005;Wang, Reimer, Dobres, & Mehler, 2014), which is thought to be a possible reason for this reduction in SDLP (Boer, Spyridakos, Markkula, & Merat, 2016;Liang et al, 2010;Victor et al, 2005), though, again, the relationship between these two particular metrics is not currently understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most popular devices utilised include electroencephalogram (EEG) sensors and the eye trackers or front camera, due to their high sensitivity and convenience for live monitoring [2], [3]. Heart rate and skin conductance level were considered reflective of cognitive load changes, and in many studies they were studied together [4], [5]. Many devices are capable of monitoring electrocardiogram (ECG) and measuring skin conductance (GSR) at the same time, such as the commonly used Vitaport Temec BV, MEDAC or Procomp Infiniti.…”
Section: Background 21 Physiological and Behavioural Sensorsmentioning
confidence: 99%
“…In addition to studies conducted at the AgeLab, the task has been used extensively internationally as a method of inducing graded levels of cognitive workload with studies such as [1,2,4,5,6,7,13,21,23,24,26,30] being conducted utilizing the English version of the task or translations into French, German, Chinese, Japanese, Swedish, Korean, and Polish. Various translations of materials provided by international research teams can be found at http://agelab.mit.edu/study-tools.…”
Section: Introductionmentioning
confidence: 99%